The researches of the influence of the Internet on the consciousness of the personality in the post-Soviet countries - Semak, Vadzim I. (Journal of the Belarusian State University. Philosophy and Psychology, 2021)
A review of the researches of the influence of the Internet technologies on the consciousness of the personality and society in the post-Soviet countries is presented. The analysis of the results of the scientific activity of the scientists in this direction. Some investigated aspects, features and consequences of the use of the online resources are revealed. Attention is focused on the ambivalence of the scientific data.
Keywords: Internet; information and communication technologies; online resources; consciousness of personality; influence; research